Transcriptome Analysis Identifies Multifaceted Regulatory Mechanisms Dictating a Genetic Switch from Neuronal Network Establishment to Maintenance During Postnatal Prefrontal Cortex Development. (20th January 2017) - Kroeze, Yvet; Oti, Martin; van Beusekom, Ellen; Cooijmans, Roel H M; van Bokhoven, Hans; Kolk, Sharon M; Homberg, Judith R; Zhou, Huiqing
Abstract: The prefrontal cortex (PFC) is one of the latest brain regions to mature, which allows the acquisition of complex cognitive abilities through experience. To unravel the underlying gene expression changes during postnatal development, we performed RNA-sequencing (RNA-seq) in the rat medial PFC (mPFC) at five developmental time points from infancy to adulthood, and analyzed the differential expression of protein-coding genes, long intergenic noncoding RNAs (lincRNAs), and alternative exons. We showed that most expression changes occur in infancy, and that the number of differentially expressed genes reduces toward adulthood. We observed 137 differentially expressed lincRNAs and 796 genes showing alternative exon usage during postnatal development. Importantly, we detected a genetic switch from neuronal network establishment in infancy to maintenance of neural networks in adulthood based on gene expression dynamics, involving changes in protein-coding and lincRNA gene expression as well as alternative exon usage. Our gene expression datasets provide insights into the multifaceted transcriptional regulation of the developing PFC. They can be used to study the basic developmental processes of the mPFC and to understand the mechanisms of neurodevelopmental and neuropsychiatric disorders. Our study provides an important contribution to the ongoing efforts to complete the "brain map", and to the understanding of PFC development.